Anticorrosive Performance of Zinc Phosphate Coatings on Mild Steel Developed Using Galvanic Coupling - M. Arthanareeswari; P. Kamaraj; M. Tamilselvi (Journal of Chemistry)
The anticorrosive performance of zinc phosphate coatings developed by galvanic coupling technique on mild steel substrates using the cathode materials such as titanium (Ti), copper (Cu), brass (BR), nickel (Ni), and stainless steel (SS) is elucidated in this study. Thermal and chemical stability tests, immersion test in 3.5% NaCl, ARE salt droplet test, and salt spray test were carried out. The study reveals that the mild steel substrates phosphated under galvanically coupled condition showed better corrosion resistance than the one coated without coupling. The open circuit potential (OCP) of phosphated mild steel panels in 3.5% NaCl was found to be a function of phosphate coating weight and porosity of the coating.